2010
DOI: 10.1111/j.1540-6210.2010.02249.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability as a Conceptual Focus for Public Administration

Abstract: Th is article argues that sustainability should defi ne the conceptual focus for the fi eld of public administration in the coming decade. Sustainability involves three systems: environmental, economic, and political/social systems. Th e challenge of governance, and thus of public administration, is to sustain each of these systems on its own while maintaining an appropriate balance among them. Th e article defi nes the sustainability concept, and its environmental component in particular, in ways that are rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 35 publications
1
113
0
17
Order By: Relevance
“…Proponents of the multidimensional view of sustainability generally identify three main dimensions of this concept -environmental, economic, and social (or sociopolitical) (Budd, et al, 2008;Dale, 2001;Edwards & Onyx, 2007;Fiorino, 2010;Nurse, 2008;Tubadji, 2010), -and some also add the technological aspect of sustainability (Hasna, 2007). For example, Edwards and Onyx attempt to reconcile three imperatives: the ecological imperative to live within global biophysical carrying capacity; the social imperative to ensure the development of democratic systems of governance to effectively promote public values; and the economic imperative to ensure that basic needs are met worldwide (Edwards&Onyx, 2007).…”
Section: The International Journal Of Sustainabilitymentioning
confidence: 99%
“…Proponents of the multidimensional view of sustainability generally identify three main dimensions of this concept -environmental, economic, and social (or sociopolitical) (Budd, et al, 2008;Dale, 2001;Edwards & Onyx, 2007;Fiorino, 2010;Nurse, 2008;Tubadji, 2010), -and some also add the technological aspect of sustainability (Hasna, 2007). For example, Edwards and Onyx attempt to reconcile three imperatives: the ecological imperative to live within global biophysical carrying capacity; the social imperative to ensure the development of democratic systems of governance to effectively promote public values; and the economic imperative to ensure that basic needs are met worldwide (Edwards&Onyx, 2007).…”
Section: The International Journal Of Sustainabilitymentioning
confidence: 99%
“…It has also been suggested that sustainability can be considered as a guiding principle in public management [4] or as a conceptual focus for public administration [31]. Sustainability initiatives and studies have long focused on cities and urban areas, with studies of American cities finding that "local sustainability is tied to local governments' need to deal with environmental pressures and the characteristics of local governance" [4] (p. 841).…”
Section: Introductionmentioning
confidence: 99%
“…DRd -Desenvolvimento Regional em debate (ISSNe 2237-9029) v. 7, n. 1, p. 214-235, maio 2017. Na área de Planejamento Urbano e Regional/Demografia, bem como na Administração Pública, os problemas urbanos de Desenvolvimento Sustentável podem ser resumidos em quatro áreas de possível insustentabilidade: serviços urbanos escassos, a degradação ambiental, escassez de recursos naturais e conflitos sociais (FIORINO, 2010;WEI et al, 2015).…”
Section: Introductionunclassified